Principles of Gene Manipulation An Introduction to Genetic Engineering - Old, R. W. Primrose, S. B. (Blackwell Scientific Publications, 1985)
The teaching of genetic engineering is now almost commonplace and an essential element in the training of a modern biologist. The development of this text reflects the change in status and growth of the subject.